WEIGHTLIFTING ELITE'S POWER SNATCH TECHNIQUE - Khasin, L.A. (Theory and Practice of Physical Culture, 2022)
The purpose of the study is to increase the effectiveness of training weightlifters and coaches. Methodology and organization of the study. Mathematical modeling (Certificate of Rospatent No. 2021662872, 06.08.2021), mathematical optimization methods, mathematical methods of data analysis were used in the study. The tools used were a Matlab computing environment; MaxTraq, Tema programs, high-speed video cameras, digital filters developed at NIIT (Certificate of Rospatent No. 2017613826, 03.04.2017). Research results and conclusions. The analysis shows the expediency of using highly qualified weightlifters when performing a jerk of the following elements of the technique: standing on toes in the depreciation phase, a powerful "rebound" of the barbell. A separate training of the unsupported phase is also recommended, which allows to reduce the bending angles in the unsupported phase and promotes the straightening of the arms in the elbow and shoulder joints.